EXPLORING CORE COMPETENCIES AND THEIR IMPACT ON ORGANIZATIONAL SUCCESS BY MEDIATING TOTAL QUALITY MANAGEMENT-AN ANALYTICAL STUDY OF A SAMPLE OF IRAQI PRIVATE COLLEGES IN BAGHDAD - Prof. Mohammad Farhat; Dina Qasim Mahdi (Scholars Digest Publishing, 2025)
This research aimed to explore core competencies and their impact on organizational success, mediated by Total Quality Management (TQM). This was done through an analytical study of a sample of Iraqi private colleges in Baghdad. The study concluded that the relationship between exploring core competencies affects the dimensions of organizational success (individually and collectively). The study indicated a positive impact of exploring core competencies on the dimensions of organizational success (individually and collectively) in the presence of TQM. It also indicated a direct, positive, and significant relationship between human competence and organizational competence. It also indicated a strong, direct, and significant correlation between the core competencies of senior management and TQM. Finally, it recommended the need to balance the internal work environment with external borrowing in order to maintain competent human resources, as human competence helps achieve sustainable competitiveness for Iraqi community colleges.
Keywords: Exploring core competencies, organizational success, TQM.